A set of ethical principles for design science research in information systems - Myers, M.; Venable, John (Elsevier BV, 2014)
Over the past decade, design science research (DSR) has re-emerged as an important research paradigm in the field of information systems. However, the approaches currently recommended for conducting design science research do not include an ethical component. Thus, the objective of this paper is to initiate a debate about the need for ethical principles for DSR in Information Systems (IS). To launch this debate, we suggest that a set of ethical principles for DSR in IS must be created. Although the interpretation and application of these principles might not always be straightforward, our argument is that all DSR practitioners in IS should devote at least some time to consider ethical principles.